2014
DOI: 10.1377/hlthaff.2013.1268
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease And Nursing Homes

Abstract: Close to two-thirds of all US nursing home residents have some type of cognitive impairment such as Alzheimer’s disease, and the quality of care and quality of life of these people has long been called into question. In this overview we first clarify the ongoing importance of nursing home care for people with Alzheimer’s, even as policy makers “rebalance” long-term supports and services with home and community-based programs. We next identify the components of optimal care for people with Alzheimer’s in nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
79
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 34 publications
1
79
1
Order By: Relevance
“…While most people with dementia live in the community, about one-third live in some type of residential care setting, either a nursing home (assuming two-thirds of nursing home residents have dementia)[9,25] or another type of residential care (Exhibit 2). As nursing home residence among people ages sixty-five and older who need long-term services and supports continues to decline,[30] residential care alternatives for providing these services have grown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most people with dementia live in the community, about one-third live in some type of residential care setting, either a nursing home (assuming two-thirds of nursing home residents have dementia)[9,25] or another type of residential care (Exhibit 2). As nursing home residence among people ages sixty-five and older who need long-term services and supports continues to decline,[30] residential care alternatives for providing these services have grown.…”
Section: Discussionmentioning
confidence: 99%
“…Half to two-thirds of nursing home residents have dementia. [9,10] The condition is thought to be equally prevalent in assisted living facilities. [11]…”
mentioning
confidence: 99%
“…For example, at baseline 4.6% of persons reported a dementia diagnosis, compared to estimates that suggest 14% of community-dwelling adults over 71 have dementia (Plassman et al, 2007). Further, nursing home residents, who have an even higher prevalence of dementia (Gaugler, Yu, Davila, & Shippee, 2014), were excluded from this analysis. Therefore, it is likely the observed relationship would remain if the sample included institutionalized adults.…”
Section: Discussionmentioning
confidence: 99%
“…LOS, successful discharge, and becoming a long‐stay resident did not seem to vary according to obesity level until we accounted for dementia and cognitive impairment. Dementia confounds the association between obesity and these outcomes because it is a risk factor for being frail or underweight and for outcomes related to nursing home LOS . After controlling for dementia and other covariates, we found that obesity conferred a strong risk for all outcomes.…”
Section: Discussionmentioning
confidence: 68%